Role of Glia in Stress-Induced Enhancement and Impairment of Memory - Pearson-Leary, Jiah; Osborne, Danielle Maria; McNay, Ewan C. (Frontiers in Integrative Neuroscience, 2016)
Both acute and chronic stress profoundly affects hippocampally-dependent learning and memory: moderate stress generally enhances, while chronic or extreme stress can impair, neural and cognitive processes. Within the brain, stress elevates both norepinephrine and glucocorticoids, and both affect several genomic and signaling cascades responsible for modulating memory strength. Memories formed at times of stress can be extremely strong, yet stress can also impair memory to the point of amnesia. Often overlooked in consideration of the impact of stress on cognitive processes, and specifically memory, is the important contribution of glia as a target for stress-induced changes. Astrocytes, microglia, and oligodendrocytes all have unique contributions to learning and memory. Furthermore, these three types of glia express receptors for both norepinephrine and glucocorticoids and are hence immediate targets of stress hormone actions. It is becoming increasingly clear that inflammatory cytokines and immunomodulatory molecules released by glia during stress may promote many of the behavioral effects of acute and chronic stress. In this review, the role of traditional genomic and rapid hormonal mechanisms working in concert with glia to affect stress-induced learning and memory will be emphasized.